IMAM AL-BUKHARI IS THE SULTAN OF THE SCIENCE OF HADITH, THE CHIEF OF MUHADDIS - Farida , Azamatovna Qalandarova (Innovative Development in Educational Activities, 2023)
This case provides information about the knowledge and habits of Imam Bukhari, the author of the collection of sahih hadiths. Bukhari had a strong memory and memorized 100000 authentic and 200000 non-authentic hadiths. In Baghdad and Samarkand, the sanad and texts of the hadiths were changed, and when they were examined, they corrected the mistakes with the help of their strong memory, and it was mentioned that they surprised those present.